Student Access to and Skills in Using Technology in an Open and Distance Learning Context - Liebenberg, Hanlie; Chetty, Yuraisha; Prinsloo, Paul (International Review of Research in Open and Distributed Learning, 2012)
Amidst the different challenges facing higher education, and particularly distance education (DE) and open distance learning (ODL), access to information and communication technology (ICT) and students’ abilities to use ICTs are highly contested issues in the South African higher education landscape. While there are various opinions about the scope and definition of the digital divide, increasing empirical evidence questions the uncritical use of the notion of the digital divide in South African and international higher education discourses. In the context of the University of South Africa (Unisa) as a mega ODL institution, students’ access to technology and their functional competence are some of the critical issues to consider as Unisa prepares our graduates for an increasingly digital and networked world. This paper discusses a descriptive study that investigated students’ access to technology and their capabilities in using technology, within the broader discourse of the “digital divide.” Results support literature that challenges a simplistic understanding of the notion of the “digital divide” and reveal that the nature of access is varied.